Translation as an Act of Intercultural Communication - Dekanozishvili, Tsiuri ("Intercultural Dialogues" Transactions, 2023)
The article "Translation as an Act of Intercultural Communication" deals with the process of translation as a communicative act and the difficulties associated with it; Types of linguistic competence in the communication are analysed. Practical ways of translation are being found to minimize the possible obstacles in the translation process; The article focuses on translation as a form of intercultural communication.